Dolichochorus Strobl 1904: a valid genus of Mesochorinae (Hymenoptera: Ichneumonidae: Mesochorinae) - Broad, Gavin R.; Watanabe, Kyohei (Zootaxa, 2019)
Dolichochorus Strobl 1904, is shown to be a valid genus of the ichneumonid subfamily Mesochorinae, and a senior synonym of Thamester Wahl 1993 (syn. nov.). Dolichochorus japonicus (Wahl 1993) is a new combination. Dolichochorus longiceps (Strobl 1904) is shown to be a senior synonym of Astiphromma elongatum Nakanishi 1969, syn. nov. The genus Dolichochorus is defined, a revised diagnosis provided for the genus and the two included species are provisionally separated.